A simple technique for isolation of DNA suitable for PCR amplification from cytogenetic preparations - Vannucci Nunes, M. [UNESP]; Barbosa De Melo, M. [UNESP]; Ferreira Costa, F. [UNESP]; Varella-Garcia, M. [UNESP] (My University, 1995)
In order to rescue molecular information from chromosome preparations, we describe a rapid procedure to obtain DNA from cytogenetic preparations in microscope slides, stored for one to five years at room temperature. This technique was modified from previously described procedures and the DNA obtained was shown to be suitable for PCR amplification.